Study of rotavirus genotypes G and P in one Egyptian center-cross-sectional study - AbelRahman Eid Mahmoud; Maysaa El Sayed Zaki; Eman Hamdy Mohamed; Ehab M. Fahmy; Sanaa Samir Mohamed Hamam; Mona Abdellatif Alsayed (BMC, 2024)
Abstract Background Rotavirus-associated gastroenteritis is a common health problem in children, different variations of rotavirus genotypes differ according to geographic locations and the practice of wide-scale vaccination. Therefore, the present study aimed to detect both the G and P genotypes of rotavirus in children ≤ 5 years old in one center in Egypt as a cross-sectional study, to correlate the genotypes with various demographic and clinical data in infected children and to evaluate the common mixed genotypes G and P in infected children. Method The cross-sectional study included children with acute gastroenteritis ≤ 5 years old from January 2023 till March 2024 recruited from Mansoura University Children's Hospital, Egypt based upon laboratory diagnosis by exclusion of bacterial and protozoa pathogens. The stool samples were obtained from each child and subjected to detection of rotavirus antigen by enzyme-linked immunosorbent assay (ELISA) followed by genotypes identification of G and P genotypes by nested polymerase chain reaction (PCR). Result A nested PCR study for rotavirus genotypes revealed that G1 was the most common genotype (24.7%) followed by G2 (21.1%), G3 (20%), G9 (20%), and G4 (14.1%). The genotyping of the P genotype revealed that P9 was the commonest genotype (24.7%), followed by P4 (21.2%), P10 (20%), P8 (17.6%) and P6 (16.5%). The commonest combined genotypes of G and P were G1P4 (85.7%), G3P8(88.2%), followed by G2P6 (77.8%) and G9P9(76.5%) and G4P9 (66.7%) followed by G4P10 (33.3%), G9P10(23.5%), G2P10(22.2%), G1P10 (14.3%), G3P10(11.8%). The distribution was significant (P = 0.001). The positive rotavirus antigen was more frequently detected in females (55.3%) than males (44.7%, Odd ratio 0.2, 95% CI 0.22-0.71, P = 0.001). There was a significant association between the summer season and positive rotavirus antigen (P = 0.001) and rural residence of the patients (Odd ratio 6,9 95%CI 3,5-13.5, P = 0.001). The significant associated clinical sign with positive rotavirus antigen was fever (Odd ratio 3,3, 95%CI 1,8-6.05, P = 0.001). The genotypes G and P were significantly associated with positive rotavirus antigen as all cases positive by antigen had been detected by nested PCR with the commonest genotypes G4 (24.7%, P = 0.001) and genotype P9 (24.7%, P = 0.001). Conclusion The present study highlights the common genotypes of rotavirus at one center in Egypt, G1, G2, and G3 were the commonest G genotypes. As regard genotype P the commonest genotypes were P9, P4, and P10. The commonest combined genotypes were G1P4, G3P8, G2P6. There was no effect of the practice of rotavirus vaccination at limited rates at private health sections as the rotavirus is still a major pathogen of acute gastroenteritis in children. There is a need for the inclusion of rotavirus vaccination in the national program of children vaccination in Egypt.